Intracerebral hemorrhage with tentorial herniation: Conventional open surgery or emergency stereotactic craniopuncture aspiration surgery? - Shi Jing (De Gruyter, 2021)
To observe the therapeutic effect of conventional decompressive craniectomy with hematoma evacuation and frame-based stereotactic minimally invasive surgery (MIS) for supratentorial intracranial hematoma with herniation.